2004
DOI: 10.1007/s00167-003-0464-6
|View full text |Cite
|
Sign up to set email alerts
|

BTB ACL reconstruction: femoral nerve block has no advantage over intraarticular local anaesthetic infiltration

Abstract: Fifty patients were randomly recruited to receive either femoral nerve block (0.375% Bupivacaine) or an intraarticular local anaesthetic injection for pain control for arthroscopically-assisted ACL reconstruction. Both groups were evenly matched for age ( t-test p >0.05). Tourniquet time did not differ significantly between the groups ( t-test p=0.24). The VAS pain levels were not significantly different at 4 h and the first morning postoperatively in both groups. Femoral block (Median VAS: 20 & 18.5) did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 19 publications
(35 reference statements)
1
47
0
3
Order By: Relevance
“…15,30 Frost and colleagues 15 reported that a single-injection bupivacaine femoral nerve block in addition to an intra-articular injection of bupivacaine administered immediately before ACL reconstruction appeared to decrease pain on the night of surgery when compared with an intra-articular injection of bupivacaine with a sham block, but the effect was clinically irrelevant in the authors' opinion. In that study, the femoral nerve block did not affect postoperative narcotic use or any of the pain ratings recorded on postoperative days 2 and 3.…”
Section: Discussionmentioning
confidence: 95%
“…15,30 Frost and colleagues 15 reported that a single-injection bupivacaine femoral nerve block in addition to an intra-articular injection of bupivacaine administered immediately before ACL reconstruction appeared to decrease pain on the night of surgery when compared with an intra-articular injection of bupivacaine with a sham block, but the effect was clinically irrelevant in the authors' opinion. In that study, the femoral nerve block did not affect postoperative narcotic use or any of the pain ratings recorded on postoperative days 2 and 3.…”
Section: Discussionmentioning
confidence: 95%
“…L'efficacité de l'analgésie par cathéter intra-articulaire a déjà été prouvée par de nombreuses études [3][4][5][6][7][8]. En 2004, Mehdi et al [3], pour les reconstructions ligamentaires du genou, ne retrouvaient aucune différence significative en termes de douleur entre un groupe traité par cathéter fémoral périnerveux et un groupe traité par cathéter intra-articulaire avec infusion continue de bupivacaïne.…”
Section: Discussionunclassified
“…En 2004, Mehdi et al [3], pour les reconstructions ligamentaires du genou, ne retrouvaient aucune différence significative en termes de douleur entre un groupe traité par cathéter fémoral périnerveux et un groupe traité par cathéter intra-articulaire avec infusion continue de bupivacaïne. De même dans la chirurgie arthroscopique de l'épaule, Klein et al [6] retrouvaient moins de douleur dans le groupe avec une perfusion intra-articulaire continue de ropivacaïne que dans le groupe avec infusion intra-articulaire de placebo.…”
Section: Discussionunclassified
“…The efficacy of preemptive, intraarticular injections of local anesthetic with or without morphine has been demonstrated in multiple prospective, randomized trials with respect to reduction of postoperative pain and narcotic use. 2,25,34,55,72,87,88 The addition of morphine to preemptive intraarticular injection of bupivacaine may improve analgesia and reduce postoperative narcotic requirement to a more significant extent than preemptive injection of bupivacaine alone. 88 Regional anesthesia techniques such as a femoral nerve block can provide excellent analgesia, but carry with them risks of prolonged nerve dysfunction with attendant paralysis of the extensor mechanism.…”
Section: Analgesiamentioning
confidence: 98%